Analytical Study of Powder Stream Geometry in Laser-Based Direct Energy Deposition Process with a Continuous Coaxial Nozzle - Qipeng Liu (MDPI AG, 2021)
In the process of laser-based direct energy deposition, the particle concentration distribution and geometric characteristics of powder flow play an important role in laser–powder interaction and powder utilization, and they affect the forming quality and accuracy. In the current study, based on the geometry information of a powder nozzle and the divergence angles of a powder jet at the nozzle outlet, the geometric profile of a powder stream is analyzed. A set of formulas for calculating the geometric characteristics of the powder stream is derived based on an analytic geometry method. The influence of each parameter on the geometric characteristics of the powder stream is further studied using single-factor and sensitivity analyses. Validation is performed by comparing the results from the presented analytical expressions with those from experiments and/or simulations in published papers. The analytical formulas provided in this paper are simple and practical, providing a theoretical foundation for the control of powder flow and related processes in the forming process.